Branching Out with DNA Helicases - Yusufzai, Timur (2011)
The proper resolution of branched DNA molecules, which arise during processes such as DNA replication, DNA repair, and transcription, is critical for the maintenance of the genome. Disruption of this process can lead to genome instability and cancer progression. In this review, we describe recent progress on several interesting and biologically important enzymes that act upon different types of branched DNA substrates.